2021
DOI: 10.3390/nano11113007
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Quenching of Excitons in the ZnxCd1−xS/ZnS Quantum Dots Doped with Mn2+ through Charge Transfer Intermediates Results in Manganese Luminescence

Abstract: For the first time, a specific time-delayed peak was registered in the femtosecond transient absorption (TA) spectra of ZnxCd1−xS/ZnS (x~0.5) alloy quantum dots (QDs) doped with Mn2+, which was interpreted as the electrochromic Stark shift of the band-edge exciton. The time-delayed rise and decay kinetics of the Stark peak in the manganese-doped QDs significantly distinguish it from the kinetics of the Stark peak caused by exciton–exciton interaction in the undoped QDs. The Stark shift in the Mn2+-doped QDs de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Additionally, ultrafast spectroscopy, which makes use of femto- to attosecond pulses of light to study the transient absorption spectra photodynamics of various materials, has also become an emerging technique that is capable of further analyzing the host–Mn interaction . Recent studies have reported ultrafast data about the charge-transfer dynamics of Mn-doped NCs containing Cd or Pb. The current understanding of the physics behind the energy transfer in Mn-doped multinary NCs as discussed in this paper is very limited. However, ultrafast spectroscopy may allow researchers to investigate the electronic transitions occurring in the band gap and the subsequent Mn ion electron spin-flip transition in-depth.…”
Section: Perspectivementioning
confidence: 99%
“…Additionally, ultrafast spectroscopy, which makes use of femto- to attosecond pulses of light to study the transient absorption spectra photodynamics of various materials, has also become an emerging technique that is capable of further analyzing the host–Mn interaction . Recent studies have reported ultrafast data about the charge-transfer dynamics of Mn-doped NCs containing Cd or Pb. The current understanding of the physics behind the energy transfer in Mn-doped multinary NCs as discussed in this paper is very limited. However, ultrafast spectroscopy may allow researchers to investigate the electronic transitions occurring in the band gap and the subsequent Mn ion electron spin-flip transition in-depth.…”
Section: Perspectivementioning
confidence: 99%
“…S8). The PA signal was not observed in CdZnS QDs without the ZnS shell, 54 and the decay lifetime of the PA signal is much longer than the biexciton transition. 64 This PA band can therefore be assigned to the excited-state absorption (EAS) of the interface-related trapping state.…”
Section: Resultsmentioning
confidence: 91%
“…S7 (ESI †). The 0.3-0.4 ps HER rate in Cd 1Àx Zn x S/ZnS is basically the same as CdZnS QDs without the ZnS shell, 54 indicating that the energy released during the electron Auger relaxation is used to excite the hole in the CdZnS core of the core/shell QDs. A positive absorption band can be seen around 470 nm before 0.2 ps.…”
Section: Transient Absorption Of CD 1àx Zn X S/zns Qds At Room Temper...mentioning
confidence: 86%
“…The transient absorption spectrum of 0.4 mg/mL QD solutions with 266 nm excitation is shown in Figure d. The transient absorption spectra give mainly positive excited-state absorption signals which can be attributed to the absorption by charge carriers trapped in the defect state. …”
Section: Resultsmentioning
confidence: 99%